SISTEM INFORMASI LOKASI INDUSTRI DI KABUPATEN SERANG BERBASIS GEOGRAPHIC INFORMATION SYSTEM (GIS) - Ariandono, Yogi; Hamzah, Amir; Nurnawati, Erna Kumalasari (Jurnal Script, 2014)
ABSTRACTIndustry spread in Serang very diverse . In general, the industry is located in Serang is a huge industry , while for small industries were not many . But the potential of this industry has not been widely known by the public his special helpers to facilitate the working world . One of the obstacles is lack of information about the location of industry . Therefore, it is necessary Serang regency industry website based Geographic Information System ( GIS ) that would assist and facilitate both the users wherever they are in order to obtain information and local government district of Serang regional promotion side. GIS can be one of the main tools are interactive , because with the GIS will be described also the location where the actual conditions in the industry in the form of a map. The process of making a website need to be more interesting and conveyed information quickly , accurately and efficientl. With this information system can display industry Serang Serang information about the industry in the form of photo galleries , industry descriptions , contact the communications industry as well as the location and distance of the nearest auto industry .Keywords : Systems , Information , Location , Industry , GIS , District